PERILAKU MALAS BELAJAR MAHASISWA DI LINGKUNGAN KAMPUS UNIVERSITAS TRUNOJOYO MADURA - Mei Mita Bella; Luluk Widya Ratna (Universitas Trunojoyo Madura, 2018)
ABSTRACTThe behavior the lazy learning, campus environment The background of this study is that there is a phenomenon Trunojoyo Madura University students who have lazy learning behavior. In connection with this problem the researcher views that the lazy behavior of students learning Trunojoyo Madura University related to the environment. The formulation of the problem in these study are: (1) what are the factors that cause student learning lazziness? (2) how are the forms of student lazy learning behavior? As for the purpose in this study is (1) knowing the factors that cause lazy student learning, (2) find out the factors that cause lazy student learning. We only observe on the campus of the Trunojoyo Madura University whose subjects are students Trunojoyo Madura University. After we made the observations, the author uses data analysis with qualitative descriptive. After being analyzed, then the conclusion is obtained, that there is a lazy attitude to studying students in the campus of Trunojoyo Madura University, the cause of lazy student learning arises from within the student (internal) and from the outside (external). Because internally, among others, because of fatigue, tiredness and no motivation to learn. Because Externally, among others, because lecturers are less attractive in delivering lectures, the habits of friends in boarding houses are rarely studied. In the campus environment also found that there were some students who were lazy to learn. From various theories that exist that the environment has an influence on one's attitudes and behavior. This article is useful for writers to gain insight into the mindset, attitude and experience as an effort to improve the spirit of learning. For Trunojoyo Madura University as a contribution to scientific thought in the context of fostering students,